System identification for small scale fisheries development in Riau Province waters - T. Ersti Yulika Sari (Syiah Kuala University, 2012)
System identification for small scale fisheries development was designed using System Methodology. This system identification consisted of construction related Causal Loop Diagram and Input-Output Diagram. It was foundthat system approach was an effective tool in identifying an complicated system. It could provide a set of holistic information necessary for solving such intricate problem systematically. The study conclude that beside favorableincentives created by the Government, accurate information along with a synergetic network among the actors involved were the key elements to develop small scale fisheries. Accurate information were needed on business forsmall scale fisheries and industrial capacity on the effectiveness of suitable fisheries and also for the processing technology, on the quality and quantity of accessible raw materials could be on the proper product prices and finallyon the appropriateness of labor wages. The system development should also explore a control subsystem to repress trade monopoly practices, diminution in product quality, excessive payment transaction and damage of theenvironment.